Spontaneous intracranial hypotension in young and middle-aged patients with chronic subdual hematoma in Korea: three case reports - Ae Ryoung Lee; Yun Suk Choi (Journal of Trauma and Injury)
This case series highlights chronic subdural hematoma in previously healthy young and middle-aged patients, where symptoms persisted despite initial surgical intervention. Subsequent diagnosis revealed spontaneous intracranial hypotension through computed tomography myelography. All patients experienced symptom relief after undergoing epidural blood patch. In conclusion, spontaneous intracranial hypotension should be considered in chronic subdural hematoma cases without trauma or underlying disease, with epidural blood patch recommended before surgical intervention if spontaneous intracranial hypotension is suspected.